THE EFFECT OF ROAD INFRASTRUCTURE DEVELOPMENT ON THE WELFARE OF THE COMMUNITY IN KAYU ARA VILLAGE, TULUNG SELAPAN REGENCY, OKI REGENCY, SELATAN SUMATRA - Sindy Astuti; Ranti Yusmania; Nesha Alifia Jauzi; Maya Panorama (Penerbit Lafadz Jaya, 2022)
The development of facilities and infrastructure in South Sumatra has been very good and has also been realized. however, in some villages, road infrastructure development still needs more attention, especially in Kayu Ara village, Kec. Tulung Selapan Kab. OIC South Sumatra. The existence of infrastructure is a very important thing especially regarding the construction of roads, because one of the daily needs to carry out various activities such as school, work is even very important if there is an emergency such as giving birth, shortness of breath and so on. However, until now the village has not been touched by the attention of both the OIC governor and the regional government. The data used in this training is primary data obtained from the party providing information directly and has not been processed. By researching directly in the field and asking various questions to respondents. With this research, it is hoped that the government will pay more attention and provide solutions that are right on target.